Application of nonlinear regression models for prediction of cardinal temperatures in seed germination of various cumin (Cuminum cyminum) ecotypes - M. Habibzadeh Zarandi; I. Allahdadi; H. Khalaj; M.R. Labbafi (علوم و فناوری بذر ایران)
This study was done to evaluate different nonlinear regression models to describe the response of germination rate and to determinate the cardinal temperature of four ecotypes of Cuminum cyminum(Cumin) seeds. This experiment was arranged in the form of three-factor factorial completely randomized design with 4 replications at the Agronomy Laboratory  (Aburaihan College, University of Tehran) in 2011.The seeds were treated with different temperatures (0, 5, 15, 25, 35 and 45 oc) and the germination rate were calculated. The result showed that the temperature had a significant effect on germination rate of all plants. The segmented model was superior compared to other models in ecotypes of cumin since the minimum amount of AICc and maximum value of Adj R2 were related to this model. Base (Tb), optimum (To) and ceiling (Tc) temperatures were predicted with appropriate models. Tb, To, and Tc for Khorasani ecotype were 0, 11.4, 25 °C; for Krmani ecotype were 0, 11.5, 28.9 °C, for Jandaghi ecotype were 3.1, 9.6, 27.1 °C and for Esfahan ecotype 0, 10.1, 35.5 °C, respectively. It was concluded that this model can be used to quantify response of cumin seed germination to temperature and to obtain the proper cardinal temperatures of germination.